Proof -
So, in the first part we'll verify by taking n = 1.
![\implies \: 1 = {1}^{2} = \frac{1(1 + 1)(2 + 1)}{6}](https://tex.z-dn.net/?f=%20%5Cimplies%20%5C%3A%201%20%20%3D%20%20%7B1%7D%5E%7B2%7D%20%20%3D%20%20%5Cfrac%7B1%281%20%2B%201%29%282%20%2B%201%29%7D%7B6%7D%20)
![\implies{ \frac{1(2)(3)}{6} }](https://tex.z-dn.net/?f=%20%5Cimplies%7B%20%5Cfrac%7B1%282%29%283%29%7D%7B6%7D%20%7D)
![\implies{ 1}](https://tex.z-dn.net/?f=%5Cimplies%7B%201%7D)
Therefore, it is true for the first part.
In the second part we will assume that,
![\: { {1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} = \frac{k(k + 1)(2k + 1)}{6} }](https://tex.z-dn.net/?f=%20%5C%3A%20%7B%20%20%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%3D%20%20%5Cfrac%7Bk%28k%20%2B%201%29%282k%20%2B%201%29%7D%7B6%7D%20%20%7D)
and we will prove that,
![\sf{ \: { {1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k + 1)(k + 1 + 1) \{2(k + 1) + 1\}}{6}}}](https://tex.z-dn.net/?f=%5Csf%7B%20%5C%3A%20%7B%20%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%20%5Cfrac%7B%28k%20%2B%201%29%28k%20%2B%201%20%2B%201%29%20%5C%7B2%28k%20%2B%201%29%20%2B%201%5C%7D%7D%7B6%7D%7D%7D)
![\: {{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k + 1)(k + 2) (2k + 3)}{6}}](https://tex.z-dn.net/?f=%20%5C%3A%20%7B%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%20%3D%20%20%5Cfrac%7B%28k%20%2B%201%29%28k%20%2B%202%29%20%282k%20%2B%203%29%7D%7B6%7D%7D)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{k (k + 1) (2k + 1) }{6} + \frac{(k + 1) ^{2} }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7Bk%20%28k%20%2B%201%29%20%282k%20%2B%201%29%20%7D%7B6%7D%20%2B%20%20%5Cfrac%7B%28k%20%2B%201%29%20%5E%7B2%7D%20%7D%7B6%7D%20)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{k(k+1)(2k+1)+6(k+1)^ 2 }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7Bk%28k%2B1%29%282k%2B1%29%2B6%28k%2B1%29%5E%202%20%7D%7B6%7D%20)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k+1)\{k(2k+1)+6(k+1)\} }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7B%28k%2B1%29%5C%7Bk%282k%2B1%29%2B6%28k%2B1%29%5C%7D%20%7D%7B6%7D)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k+1)(2k^2 +k+6k+6) }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7B%28k%2B1%29%282k%5E2%20%2Bk%2B6k%2B6%29%20%7D%7B6%7D%20)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k+1)(2k^2+7k+6) }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7B%28k%2B1%29%282k%5E2%2B7k%2B6%29%20%7D%7B6%7D%20)
![{1}^{2} + {2}^{2} + {3}^{2} + ..... + {k}^{2} + (k + 1)^{2} = \frac{(k+1)(k+2)(2k+3) }{6}](https://tex.z-dn.net/?f=%7B1%7D%5E%7B2%7D%20%2B%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20%20%2B%20.....%20%2B%20%20%7Bk%7D%5E%7B2%7D%20%20%2B%20%28k%20%2B%201%29%5E%7B2%7D%20%3D%20%5Cfrac%7B%28k%2B1%29%28k%2B2%29%282k%2B3%29%20%7D%7B6%7D%20)
<u>Henceforth, by </u><u>using </u><u>the </u><u>principle </u><u>of </u><u> mathematical induction 1²+2² +3²+....+n² = n(n+1)(2n+1)/ 6 for all positive integers n</u>.
_______________________________
<em>Please scroll left - right to view the full solution.</em>
Answer: 10y + 1
Step-by-step explanation:
The perimeter is the total distance round the figure.
Now, in this case it is going to be
Perimeter = 3y + 5 + 6y + y - 4
= 3y + 6y + y + 5 - 4
= 10y + 1
<span>a rectangle of dimensions 1 cm * 50 cm has a perimeter of 102 cm.</span>
Answer:
B
Step-by-step explanation:
let base be b then height h = 2b + 4
The area (A) of a triangle is calculated as
A =
bh ( b is the base and h the height ) , then
A =
b(2b + 4) ← distribute parenthesis
A = b² + 2b
When b = 16 , then
A = 16² + 2(16) = 256 + 32 = 288 in²